MEMPREDIKSI KINERJA PEGAWAI DINAS PERTANIAN PROVINSI BANTEN BERDASARKAN PERAN KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA NON FISIK DAN SUBJECTIVE WELL-BEING - Yudi Yudi Sugiarto; Ipah Ema Jumiati; Rina Yulianti (Jurnal Kebijakan Pembangunan Daerah, 2023)
The success of the public bureaucracy in carrying out its duties is largely determined by the leadership, the non-physical work environment and the happiness of its employees. This study aims to determine the performance of Banten Provincial Agriculture Service employees through the role of transformational leadership, non-physical work environment and subjective well-being. Non-experimental quantitative methods were used in this study with a sample of 192 employees. The results of the study show that transformational leadership, non-physical work environment, and subjective well-being either partially or simultaneously have a significant positive effect on employee performance. The three variables simultaneously affect employee performance by 67.5%, while the remaining 32.5% are influenced by other variables outside of this study. The transformational leadership variable is the variable that has the most role in predicting employee performance (0.381) compared to subjective welfare variables (0.341) and non-physical work environment (0.180).